Exosomal MiRNAs in Pediatric Cancers - Galardi, Angela (Int J Mol Sci, 2019)
MicroRNAs (miRNAs) have generated great attention in oncology as they play a fundamental role in the regulation of gene expression and their aberrant expression is present in almost all types of tumors including pediatric ones. The discovery that miRNAs can be transported by exosomes, which are vesicles of 40–120 nm involved in cellular communication, that are produced by different cell types, and that are present in different biological fluids, has opened the possibility of using exosomal miRNAs as biomarkers. The possibility to diagnose and monitor the progression and response to drugs through molecules that can be easily isolated from biological fluids represents a particularly important aspect in the pediatric context where invasive techniques are often used. In recent years, the idea of liquid biopsy as well as studies on the possible role of exosomal miRNAs as biomarkers have developed greatly. In this review, we report an overview of all the evidences acquired in recent years on the identification of exosomal microRNAs with biomarker potential in pediatric cancers. We discuss the following herein: neuroblastoma, hepatoblastoma, sarcomas (osteosarcoma, Ewing’s sarcoma and rhabdoid tumors, and non-rhabdomyosarcoma soft tissue sarcoma), brain tumors, lymphomas, and leukemias.